High performance liquid chromatography assay for determination of moxifloxacin in human plasma - Hanh, Luong Thi My; Diep, Nguyen Thi Minh; Ngoc Mai, Pham Thi; Truong, Nguyen Xuan (Vietnam Journal of Science and Technology, 2019)
A simple reversed phase HPLC method with UV detection has been successfully developed and validated for determination of moxifloxacin in human plasma. The sample pretreatment involves only single-step protein precipitation with tricloroacetic acid. Moxifloxacin was measured in plasma using a validated HPLC method with UV detector at 295 nm, C18 column (25cm×4.5mm, 5µm), a mixture of phosphate buffer pH 4.0 and acetonitrile (70:30, v/v) as mobile phase at a flow rate of 0.8 ml/min. Retention time of moxifloxacin was found to be 7.4 min. The mean recovery for the drug was obtained 97.30%. The calibration curve was linear over the concentration range of 0.3 to 25.0 µg/mL with coefficient correlation of 0.9991. This method was successfully applied for therapeutic drug monitoring.